PENGARUH PRICE DAN SERVICE QUALITY TERHADAP CUSTOMER LOYALTYPADA BLACK DEW CAFE PACET MELALUI CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING - Fitri Dhea Lusanti; Mei Indrawati; Indra Prasetyo (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2026)
This study is based on the phenomenon that occurs where customer loyalty problems faced by Black Dew Café Pacet are in the midst of variations in customer perception of price and service quality. The problem in this study is